1993
DOI: 10.1016/0370-2693(93)90139-9
|View full text |Cite
|
Sign up to set email alerts
|

Corrections to bino annihilation. I. Sfermion mixing

Abstract: We consider corrections to bino annihilation due to sfermion mixing.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
24
1

Year Published

1994
1994
1996
1996

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 45 publications
0
24
1
Order By: Relevance
“…(This upper limit is somewhat dependent on the value of of the top quark mass. In [7,9], we found that the upper limit was ∼ 250 GeV for m t ∼ 100 GeV. When m t = 174 GeV, the upper limit is 260 GeV.…”
mentioning
confidence: 94%
See 4 more Smart Citations
“…(This upper limit is somewhat dependent on the value of of the top quark mass. In [7,9], we found that the upper limit was ∼ 250 GeV for m t ∼ 100 GeV. When m t = 174 GeV, the upper limit is 260 GeV.…”
mentioning
confidence: 94%
“…As the bino mass is increased, there is an upper limit m B < ∼ 250 GeV [7,8]. In [9], it was shown that this upper limit is sensitive to the level of sfermion mixing. Here, we find that the upper limit to the bino mass is relaxed when phases in the MSSM, and in particular the phases associated with the off-diagonal sfermion masses, are allowed to take non-zero values.…”
mentioning
confidence: 99%
See 3 more Smart Citations